HOMONYMY BETWEEN HOMOGRAPH WORDS AND ITS SYNTACTIC CATEGORIES IN COMMON WORDS OF SUNDANESE AND JAVANESE - Adams, D.M., & Hamm, M.E. 1989.Media and Mahdi; Dean Raiyasmi (Proceeding of International Conference on Art, Language, and Culture, 2017)
This research analyses the semantic process in two local languages; Sundanese and Javanese existed in Indonesia, which is focused on homonymy. This research is aimed to find the homonymy in form of homograph in common words which is existed in both languages and how many homographs that have similar syntactic category. The methodology used in this research is qualitative where participative observation is employed first and later on structured interview is employed. The results shows that there are nine homographs which are homonymy between languages despite some of them share similar syntactic categories, however, the meaning is completely different from one to another.